Macroscopic Anatomy of the Layered Structures of Facial Muscles and Fasciae in the Temporal-Malar-Mandible-Neck Region. Issue 7 (2nd October 2022) - Takami, Hisako; Hayashi, Takafumi; Sato, Noboru; Ohshima, Hayato
Abstract : The layered structures of facial muscles and their topographical relationship with facial fasciae are still not fully understood. This study aimed to clarify the layered structures of facial muscles and fasciae in the temporal-malar-mandible-neck region. Thirty-four human cadavers were examined during gross anatomy courses at Niigata University (2017–2020). The face was composed of 3-layered (deep, middle, and superficial) fasciae and 4-layered facial muscles (first superficial, second superficial, third, and fourth muscle layers) according to the attachment of muscles and their topographical relationship with the fasciae. The deep fascia covered the temporal and masseter muscles. The parotid gland and facial nerves were enveloped in the middle fascia. The superficial fascia was continuous with the second superficial muscle layer. The connection between fourth and superficial muscles was at the malar and buccal areas, where the platysma blended with the masseter and the plural muscles blended with the buccinator. Our findings suggest that cooperation between the 4-layered structure of the facial muscles surrounding the apertures of the eyes and mouth and the superficial fascia enables humans to produce complex facial expressions. Furthermore, the spread of inflammation in the face may be owing to the layered facial muscles and fasciae, as these layered structures separate tissues into multiple compartments.